2021
DOI: 10.1155/2021/5558918
|View full text |Cite
|
Sign up to set email alerts
|

A Multilayer Perceptron Neural Network with Selective-Data Training for Flight Arrival Delay Prediction

Abstract: Flight delay is the most common preoccupation of aviation stakeholders around the world. Airlines, which suffer from a monetary and customer loyalty loss, are the most affected. Various studies have attempted to analyze and solve flight delays using machine learning algorithms. This research aims to predict flights’ arrival delay using Artificial Neural Network (ANN). We applied a MultiLayer Perceptron (MLP) to train and test our data. Two approaches have been adopted in our work. In the first one, we used his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…The multilayer perceptron algorithm takes the longest training time to classify the data based on its impairment type, which takes 3.74s to train 10-fold cross-validation. Training of MLP can be a bit of a gradual process [29] because the number of training epochs and time elapsed for total epochs indicates when the training was completed [30]. The result of classifications done using WEKA in Table 4 indicates that's random forest algorithm gives a promising result for the application of classifying fault types in ADSL copper access networks.…”
Section: Resultsmentioning
confidence: 99%
“…The multilayer perceptron algorithm takes the longest training time to classify the data based on its impairment type, which takes 3.74s to train 10-fold cross-validation. Training of MLP can be a bit of a gradual process [29] because the number of training epochs and time elapsed for total epochs indicates when the training was completed [30]. The result of classifications done using WEKA in Table 4 indicates that's random forest algorithm gives a promising result for the application of classifying fault types in ADSL copper access networks.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a failure in turnaround process caused by push-back, fueling/refueling, catering or mechanical check operations may engender delays. Personnel stress and fatigue [19] or personnel labor strike [21] are considered contributive to carrier traffic delays.…”
Section: Features Analysismentioning
confidence: 99%
“…If it is higher, the flight is likely to be late. [21] concluded that the longer is the distance, the higher is the delay. Departure Delay Departure delays are contributive to arrival delays.…”
Section: Features Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, an increase in air traffic and flight delays has become a severe and prominent issue globally [1]. Based on the United States (US) Bureau of Transportation Statistics (BTS) report, most airline flights arrived 15 min late at their destination [14][15][16][17][18][19][20][21][22], thus incurring a loss of $30 billion, which is a challenge to the air transportation system [14,23]. Delay analyses have become an important research topic, and delay prediction has been the subject of earlier studies [14,24,25].…”
Section: Introductionmentioning
confidence: 99%